Measurement of the B±c production cross section in p¯p collisions at ?s=1.96 TeV - Aaltonen, T.; Amerio, S.; Amidei, D.; Anastassov, A.; Annovi, A.; Antos, J.; Apollinari, G.; Appel, J. A.; Arisawa, T.; Artikov, A.; Asaadi, J.; Ashmanskas, W.; et al. (My University, 2016)
We describe a measurement of the ratio of the cross sections times branching fractions of the Bc+ meson in the decay mode Bc+?J/??+? to the B+ meson in the decay mode B+?J/?K+ in proton-antiproton collisions at center-of-mass energy s=1.96 TeV. The measurement is based on the complete CDF Run II data set, which comes from an integrated luminosity of 8.7 fb-1. The ratio of the production cross sections times branching fractions for Bc+ and B+ mesons with momentum transverse to the beam greater than 6 GeV/c and rapidity magnitude smaller than 0.6 is 0.211±0.012(stat)-0.020+0.021(syst). Using the known B+?J/?K+ branching fraction, the known B+ production cross section, and a selection of the predicted Bc+?J/??+? branching fractions, the range for the total Bc+ production cross section is estimated. © 2016 American Physical Society.
Citation: Aaltonen, T., Amerio, S., Amidei, D., Anastassov, A., Annovi, A., Antos, J., . . . Zucchelli, S. (2016). Measurement of the Bc± production cross section in p p collisions at s. Physical Review D - Particles, Fields, Gravitation and Cosmology, 93(5). doi:10.1103/PhysRevD.93.052001